Humic acid and chicken manure improve growth and productivity of organic edamame - Regata Ringga Hanessa Putry; Maya Melati; Munif Ghulamahdi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2025)
Edamame (Glycine max L.), a soybean harvested for young pods, has high nutritional content and is promising as an export commodity. Here, organic edamame was produced by incorporating chicken manure and humic acid. This study aimed to evaluate the effects of chicken manure, humic acid, and their interaction on the growth and productivity of edamame. The study used a factorial randomized complete block design with two factors and three replications, and it was carried out at the IPB Experimental Station, Cikarawang A, Dramaga, Bogor, from May to September 2024. The first factor was chicken manure: 0, 8, 16, and 24 tons ha-1, and the second factor was humic acid: 0, 30, 60, and 90 kg ha-1. Vegetative variables were observed at 5 weeks after planting (WAP). The relative growth rate (RGR) and net assimilation rate (NAR) were determined from the period between 3 and 5 WAP. Yield components included the number, length, and weight of pods and pod yield. The results showed that the interaction of chicken manure and humic acid significantly increased root length, RGR, number of flowers, number of productive nodes, plant fresh weight, plant dry weight, pod weight per plant, and pod yield. Chicken manure at 9.5 tons ha-1 and humic acid at 90 kg ha-1 were the optimum doses to significantly increase pod yield. This study highlights the potential use of humic acid to reduce the amount of chicken manure demand in organic farming systems. Keywords: leaf greenness; net assimilation rate; nutrient levels; organic fertilizer; relative growth rate